2021
DOI: 10.1002/jsfa.11151
|View full text |Cite|
|
Sign up to set email alerts
|

An innovative konjac glucomannan/κ‐carrageenan mixed tensile gel

Abstract: BACKGROUND Konjac glucomannan (KGM) showed a synergistic interaction with κ‐carrageenan (CAR), which led to the formation of a promising compound hydrocolloid gel in the food field (such as jelly). Nevertheless, the mixed gels formed by adding KGM to CAR still displayed defects in gel strength and syneresis, and would hardly meet the quality requirements of some gel foods. However, deacetylated KGM and maltodextrin (MD) have always been used in gel foods and affect their viscosity and rheological properties. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…KGM and κ-carrageenan (CAR) showed a synergistic effect, thus forming a composite hydrophilic gel (if frozen) with great prospects in the field of food. It was found that appropriate addition of MD (0.4%) and deacetylated KGM could change the tensile properties of KGM/CAR blend gels, which might meet the needs of consumers and further design innovative tensile gel products in the soft gel industry (Wu et al, 2021). KGM can be used as additive to improve the properties of wheat products.…”
Section: Konjac and Foodmentioning
confidence: 99%
“…KGM and κ-carrageenan (CAR) showed a synergistic effect, thus forming a composite hydrophilic gel (if frozen) with great prospects in the field of food. It was found that appropriate addition of MD (0.4%) and deacetylated KGM could change the tensile properties of KGM/CAR blend gels, which might meet the needs of consumers and further design innovative tensile gel products in the soft gel industry (Wu et al, 2021). KGM can be used as additive to improve the properties of wheat products.…”
Section: Konjac and Foodmentioning
confidence: 99%
“…According to Wang et al (2021), gels based on KGM and κ-C are more flexible and less brittle than those made by either one of the two polymers alone. KGM and κ-C are examples of the synergistic effect between two polysaccharides, and their mixtures were used to produce jelly or gelatinous food with improved texture (Wu et al, 2021). Although their combination has been already studied (Chen et al, 2019;Wu et al, 2021), it has never been 3D printed.…”
Section: Introductionmentioning
confidence: 99%
“…KGM and κ‐C are examples of the synergistic effect between two polysaccharides, and their mixtures were used to produce jelly or gelatinous food with improved texture (Wu et al ., 2021). Although their combination has been already studied (Chen et al ., 2019; Wu et al ., 2021), it has never been 3D printed.…”
Section: Introductionmentioning
confidence: 99%